Mechanical and Thermal Behavior of Epoxy Composites with Carbon Black - Noor.H. Majeed (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Polymer composites are widely developed to meet structural and functional demands through tailored fillers. Specific background: Epoxy matrices combined with particulate carbon black offer tunable mechanical strength and thermal transport. Knowledge gap: The coupled compressive response and heat conduction behavior across varied carbon black loadings, including recovery phenomena, remains insufficiently clarified. Aims: This study examines compressive strength and thermal conductivity of epoxy composites containing 0–9 wt% carbon black fabricated via hand lay-up. Results: Compressive strength peaked at 5 wt% carbon black, attributed to improved interfacial bonding and stress transfer, while higher contents reduced strength due to agglomeration. An unusual elastic-like recovery under compression occurred without catastrophic failure. Thermal conductivity increased monotonically, reaching a maximum at 9 wt% as conductive pathways developed. Novelty: The identification of pseudo-elastic recovery alongside opposing optima for mechanical strength and thermal transport provides a distinctive structure–property relationship. Implications: These findings guide composition selection for lightweight components requiring balanced load-bearing capacity and heat dissipation. Highlights Peak compressive strength achieved at 5 wt% carbon black. Elastic-like recovery observed under compressive loading. Thermal conductivity rises steadily with filler content. Keywords: Epoxy Composites; Carbon Black; Compressive Strength; Thermal Conductivity; Particle Reinforcement